If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1c + 8c + -15 + c + -5c + -6 = 0 Reorder the terms: -15 + -6 + -1c + 8c + c + -5c = 0 Combine like terms: -15 + -6 = -21 -21 + -1c + 8c + c + -5c = 0 Combine like terms: -1c + 8c = 7c -21 + 7c + c + -5c = 0 Combine like terms: 7c + c = 8c -21 + 8c + -5c = 0 Combine like terms: 8c + -5c = 3c -21 + 3c = 0 Solving -21 + 3c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 3c = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 3c = 0 + 21 3c = 0 + 21 Combine like terms: 0 + 21 = 21 3c = 21 Divide each side by '3'. c = 7 Simplifying c = 7
| 3(x-6)+4=5(x+2)-8 | | (-9x-x+2)+(4x+2x-7)= | | h+h+2=394 | | 22x-6-18x+3=20x-4-16x+13 | | -2(x-3)=3(-2x+4) | | 6(3+4x)-1=89 | | 0.86*7267-198= | | 2x^3+6x^2+x+3= | | 0.8(7267+300)= | | v^2=v+30 | | 0.8(x+300)=0.86x-196 | | (4x+1)(x+1)=7 | | 6.5x-2.8=5.2-3.5x | | 5-8y=3y+13 | | 6(3x-9)-7=6(x-2)+35 | | 4y-7+y+45=7y+40-4y | | -2=42 | | 8k+6=8k+13 | | m+30=23 | | e/7=8 | | xy=24 | | 5x-(x-5)= | | 20x^2+4x=3 | | 81-5(-4)= | | -4+9(-4)-21= | | (3x+3)(4x+4)=8x | | 2(x-8)+3(x+2)=-4x+8 | | N-15=29 | | 4n+12= | | -2(-4)-6(-4)+-4= | | f+15=+16 | | (-4)-(-4)(2)+1= |